2018
DOI: 10.1097/md.0000000000013163
|View full text |Cite
|
Sign up to set email alerts
|

Association between the aspartic acid D-repeat polymorphisms and osteoarthritis susceptibility

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…34 A recent systematic review and meta-analysis revealed that there is a significant relationship between ASPN D14 polymorphism and knee OA. 41 Taipale et al reported that the carriage of the ASPN D15 allele is associated with the increased risk of symmetrical hand OA. 22 Moreover, the D14 repeat polymorphism of the ASPN gene was found to be associated with primary OA of the knees in a Mexican Mestizo population.…”
Section: Discussionmentioning
confidence: 99%
“…34 A recent systematic review and meta-analysis revealed that there is a significant relationship between ASPN D14 polymorphism and knee OA. 41 Taipale et al reported that the carriage of the ASPN D15 allele is associated with the increased risk of symmetrical hand OA. 22 Moreover, the D14 repeat polymorphism of the ASPN gene was found to be associated with primary OA of the knees in a Mexican Mestizo population.…”
Section: Discussionmentioning
confidence: 99%
“…At present, many genes are reported to be related to the occurrence and development of OA by increasing susceptibility, enhancing cartilaginous matrix degradation, preventing cartilage from repair, increasing the expression of inflammatory factors, or promoting fibroblast transformation. First, the susceptibility genes of OA mainly include ASPN ( Wang et al, 2018 ), ADIPOQ ( Shang et al, 2019 ), AKNA ( Zhao et al, 2020a ), DPEP1 ( Zhang et al, 2021a ), rs1065080 ( Lu et al, 2019a ), TLR7 ( Wang et al, 2020a ), RTP4 ( Wang et al, 2020a ), CRIP1 ( Wang et al, 2020a ), ZNF688 ( Wang et al, 2020a ), TOP1 ( Wang et al, 2020a ), EIF1AY ( Wang et al, 2020a ), RAB2A ( Wang et al, 2020a ), ZNF281 ( Wang et al, 2020a ), UIMC1 ( Wang et al, 2020a ), and PRKACB ( Zhao, 2021 ). Second, the genes that promote the degradation of cartilage mainly include ADAMTS5 ( Jiang et al, 2021 ), ADAM12 ( Lv et al, 2017 ), JUN ( Rhee et al, 2017 ), PTGS2 ( Zhou et al, 2019a ), MMP1 ( Zhou et al, 2019a ), MMP3 ( Zhou et al, 2019a ), MMP13 ( Zhou et al, 2019a ), AGT ( Wang et al, 2020b ), and rs2830585 ( Zhou et al, 2019b ).…”
Section: Methodsmentioning
confidence: 99%
“…The encoded protein binds collagen and calcium, thus inducing collagen mineralization [8]. Additionally, ASPN regulates chondrogenesis by inhibiting transforming growth factor-β (TGF-β) gene expression that is commonly expressed in cartilaginous tissues [8,9]. ASPN contains a specific polymorphic D-repeat in the N-terminus region, ranging from 9-20 residues [6].…”
Section: Review Asporinmentioning
confidence: 99%
“…ASPN contains a specific polymorphic D-repeat in the N-terminus region, ranging from 9-20 residues [6]. There is an established association between the various D polymorphisms and increased risk of osteoarthritis, making this gene a possible candidate as a susceptibility gene to lumbar disc degeneration (LDD) [6,8,9]. A meta-analysis published in 2008 determined that the ASPN gene was shown to be upregulated with age and disc degeneration.…”
Section: Review Asporinmentioning
confidence: 99%